Maternal and foetal outcome in patients referred to tertiary care hospital: 6-month prospective study - Chaudhary, Haresh A.; Airao, Bhavesh B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Early identification, initiation of early treatment and timely referrals are the crucial components for success of any maternal and fetal health intervention to reduce the maternal and fetal mortality. Objectives of the study were: to know the incidence of referred patients to C.U. Shah Medical College and Hospital, Surendranagar; to evaluate maternal and foetal outcome in the referred patients; and to identify lacunae in appropriateness and timeliness of referral. Methods: The present study was done in department of obstetrics and gynaecology C. U. Shah Medical College and Hospital, Surendranagar, during January 2022 to June 2022 (duration of 6 months) to study the referred patients with respect to age, parity, place of referral, types of transport used, causes of referral, maternal and perinatal outcome and if maternal and fetal death occurs, identify its cause. Results: Maximum patients are primigravida and of 20-30 years of age. Majority of patients used government vehicles/108 and only few have been using private vehicles. All patients reached C. U. Shah Medical College and Hospital within 2 hours, which is adequate for management of complications unless the patients are referred timely from the referring site. About 30% of patients are referred with no high-risk factors and 80% of patients are referred during emergency hours. Conclusions: Early identification, initiation of early treatment and timely referrals are the crucial components for success of any maternal health intervention. Minimizing the causes of delay to emergency obstetric care significantly decrease maternal and neonatal morbidity and mortality.